Vitamin D and Atopic Dermatitis - M. Pacheco-Gonzalez, Rosa; W. Garcia-Marcos, Patricia; Garcia-Marcos, Luis (Mini Reviews in Medicinal Chemistry, 2015)
Atopic dermatitis is a chronic inflammatory skin disease that affects a high number of children worldwide. It is mainly caused by a disruption of the epidermal barrier and an abnormal immune response. Vitamin D might have some effects on the innate and adaptive immune system, generally in favour of decreasing allergenic mechanisms, as well as it might improve the skin barrier and decrease the risk of skin colonization. Thus, an increasing body of evidence links this vitamin to atopic dermatitis, although conclusions are not unanimous. Many observational studies have shown that low vitamin D serum levels are associated with a higher prevalence of this epidermal disease in childhood, but others have not. Differences in exposure time, vitamin D dose, age of participants, etc. could explain these conflicting results. Moreover, no study has been performed to date in order to determine whether variations in vitamin D levels at different ages differentially influence the risk of atopic dermatitis. A number of randomized controlled trials have tested the usefulness of systemic vitamin D as a treatment for this condition, but the results are also inconclusive. Nevertheless, topical vitamin D is not recommended because it can worsen skin lesions. Narrowband ultraviolet B is used to treat atopic dermatitis, although there is little evidence relating this type of phototherapy with variations of serum vitamin D levels or to what extent phototherapy benefits are mediated through vitamin D.
Keywords: Atopic dermatitis